Contamination of Arsenic Speciation in Rice: https://doi.org/10.69692/SUJMRD100110 - Lobriayao, Bounphak; Vongkhampheng, Chanhphone; Thammavong, Latsamy; Nutrue, Sengdao; Vannasy, Syphachan; Phichit, Nakhonekham; Xaiyabountha, Noynitar; Souvanhnavong, Phouvi; Menvilay, Souliphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Rice is the staple food of people in Asian countries, especially in Laos, where it is carbohydrate stuff that plays an essential role as a source of energy to support human beings. Arsenic (As) is a heavy metal of which naturally occurring; it can be found in soil, rocks, and natural water sources; and is caused by human activities such as mining activities, the use of agro-chemicals (pesticides, herbicides, etc.) in agriculture. Therefore, it is possible to deposit and contaminate the environment such as the paddy soil and the irrigation; afterward, it can initiate the arsenic residues in the agricultural productions that harvesting from the contaminated area, which is the rice grain. Furthermore, the arsenic residue can give rise to a health impact on those who consume the toxic rice. According to the analysis results of arsenic contamination in the 3 types of rice samples revealed that: in the HSV sample, the total amount of arsenic was 0.11 mg/kg, and the total inorganic arsenic (iAs) was 0.09 mg/kg which included the amount of inorganic arsenic AsV was 0.02 mg/kg, the inorganic arsenic AsIII was 0.07 mg/kg; the total arsenic in the TDK8 sample was 0.19 mg/kg, the (iAs) was 0.01 mg/kg, and the amount of arsenic AsV was 0.01 mg/kg, the amount of arsenic AsIII was 0.08 mg/kg; the total arsenic in the Composite rice was 0.14 mg/kg, the (iAs) was 0.08 mg/kg, the AsV and AsIII were 0.006 mg/kg and 0.08 mg/kg, respectively. In conclusion, the arsenic residue was contaminated in all three rice samples, but the residue of total arsenic and inorganic arsenic (iAs) did not exceed the maximum permissible limit of the international standard or CODEX which is 0.3 and 0.2 mg/kg, respectively.